International agricultural research for food security, poverty reduction, and the environment: What to expect from scaling up CGIAR investments and “Best Bet” programs - von Braun, Joachim; Fan, Shenggen; Meinzen-Dick, Ruth S.; Rosegrant, Mark W.; Nin-Pratt, Alejandro (International Food Policy Research Institute, 2008)
The recent food crisis, combined with the energy crisis and emerging climate change issues, threatens the livelihoods of millions of poor people as well as the economic, ecological, and political situation in many developing countries. On top of these crises, the decades of shrinking global investment in agricultural research are leading to slower growth in agricultural productivity. Progress in achieving development goals-such as cutting hunger and poverty in half by 2015-has been delayed significantly. In fact, the number of hungry people actually increased by at least 75 million from 2004 to 2007 and probably by even more in 2008. Investment potential in developing-country agriculture is improving, but realizing this potential requires policy action. Addressing these challenges will require the world to develop a more productive and sustainable food and agricultural system. More and more experts and policymakers agree that investment in agriculture and in related, research-based innovations must be accelerated. The Consultative Group on International Agricultural Research (CGIAR) is particularly well positioned to contribute to the global effort to foster sustainable food production, increase access to food, and reduce poverty and hunger in rural and urban areas. Its 15 international research centers generate publicly available research on everything from dryland and tropical agriculture, to livestock, to agroforestry, to water management and fisheries. They have decades of experience in agricultural research and participate in a worldwide network of partnerships. The CGIAR is now redesigning its structure and organization to address these global challenges, but it also requires increased funding.